KARAKTERISASI GALUR HIBRIDA HASIL PERSILANGAN IKAN GURAMI (Osphronemus goramy Lac.) ASAL JAMBI, KALIMANTAN SELATAN DAN JAWA BARAT BERDASARKAN METODE TRUSS MORFOMETRIK - Suharyanto Suharyanto; Rita Febrianti; Sularto Sularto; Ade Anom Abimanyu (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Giant gouramy is a native fish to Indonesia and widely distributed in Sumatra, Kalimantan and Java. The aim of this study was to characterize the phenotype and kinship of Giant Gouramy from crosses between strains Jambi, South Kalimantan, and West Java (Tasikmalaya). This Research was conducted at the Giant gouramy Hatchery of Research Institute for Fish Breeding, Sukamandi, West Java. Analysis of morphological diversity of all crosses between varieties performed through morphometric measurements that have been determined based on a point benchmark of 16 haracteristics of the truss. Measurement data of each character crosses which have beenrelativized by standard length were analyzed using discriminant analysis and hierarchical cluster analysis. The result showed that Giant gouramy has low diversity coefficient values, ranging from 4 to13%. The highest coefficient of variance (CV) was found in the character of C3 (the tip of the anal fin-base of the tail fin), which ranges from 18-33% and the lowest in the character B5 (the base of the pelvic fin-tip of the dorsal fin) in the range of 2-4%. Based on discriminant analysis, males Giant Gouramy have more character differences than females. The closest kinship relationship is in hybrid of Tasikmalaya and Jambi (TJ) strain with of South Kalimantan and Tasikmalaya ( KT) which has a similarity level at 89.41%. However, the farthest kinship is in pure line of Tasikmalaya (TT) and Jambi (JJ) with the three other strains namely South Kalimantan and Jambi (KJ), Tasikmalaya and Jambi (TJ) and South Kalimantan and Tasikmalaya (KT) with a value of similarity of 53.93%.